Indonesia and Two Great Narratives on Islamic Studies - Komaruddin Hidayat; Dadi Darmadi (Studia Islamika, 2019)
There are at least two interesting facts about Indonesia and the Muslim world. First, Indonesia is the largest Muslim country in the world. With more than 260 million people, Indonesia is the 4th most populous country in the world, and here Islam is the most adhered to religion. With approximately 87 % of its population are Muslims, the largest Muslim population in one country lives in Indonesia.Second, a large number of Muslim majority countries are not Arabs. According to the Pew Research Center, approximately 20 percent of Muslims live in Arab countries. Turkey and Iran, two non-Arab countries, are the largest Muslim-majority countries in the Middle East. Meanwhile, South Asia and Southeast Asia cover around 62 percent of the world’s Muslims. Indonesia alone is home to 12.7 percent of all world’s Muslims.These two facts show Indonesia’s unique position in the Islamic world. On the one hand, Indonesia is one of the farthest countries from the Arab World, but Islam that comes from there has been deeply rooted in the daily lives of many Indonesian Muslims. On the other hand, Indonesia which was colonized for more than three hundred years by Western colonialism, did not take for granted the influence of Arab cultures, and even more in contact with modernity, both directly and indirectly introduced by way of colonialism.